Human Trafficking and Migrant Smuggling in Southeast Europe and Russia Learning Criminal Entrepreneurship and Traditional Culture - Leman, Johan; Janssens, Stef.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2015)
Through unprecedented access to over 100 court files and sentences, and interviews with police and security personnel in both origin and destination countries, this book provides the most comprehensive exploration to date of human trafficking and migrant smuggling in Eastern Europe and Russia.
Keywords: Social sciences; Ethnology; Political science; Criminology; Crime -- Sociological aspects; Organized crime; Social justice; Human rights; Social Sciences; Organized Crime; Crime and Society; Criminology & Criminal Justice; Social Justice, Equality and Human Rights; Political Science; Cultural Anthropology; Electronic books